3(x+5)=-2(x-5)

Simple and best practice solution for 3(x+5)=-2(x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+5)=-2(x-5) equation:


Simplifying
3(x + 5) = -2(x + -5)

Reorder the terms:
3(5 + x) = -2(x + -5)
(5 * 3 + x * 3) = -2(x + -5)
(15 + 3x) = -2(x + -5)

Reorder the terms:
15 + 3x = -2(-5 + x)
15 + 3x = (-5 * -2 + x * -2)
15 + 3x = (10 + -2x)

Solving
15 + 3x = 10 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
15 + 3x + 2x = 10 + -2x + 2x

Combine like terms: 3x + 2x = 5x
15 + 5x = 10 + -2x + 2x

Combine like terms: -2x + 2x = 0
15 + 5x = 10 + 0
15 + 5x = 10

Add '-15' to each side of the equation.
15 + -15 + 5x = 10 + -15

Combine like terms: 15 + -15 = 0
0 + 5x = 10 + -15
5x = 10 + -15

Combine like terms: 10 + -15 = -5
5x = -5

Divide each side by '5'.
x = -1

Simplifying
x = -1

See similar equations:

| 4p-2(2-3p)=6(p-6)-36 | | -[8z-(14z+1)]=1+(5z+0) | | 0=x^2-4.75x+3 | | 10x^2+5-7x-6x^2-13x= | | 2*(4x-3)=3x-5 | | x^2-4.75-24=0 | | 6(x-6)-8(x+2)=-10 | | 6x-15=9+3x | | 13x+17y=19 | | 2x+10=6+4x | | -7(x+4)+4x+7=8x+6 | | 7/60=a | | 2x-16=-128 | | 1.4(x)=2x-3 | | 2/5*7/-6*-7=a | | .5(x)=2x-3 | | x+18=106 | | 2/5*7/-6*-7 | | -1(x)=2x-3 | | 1(x)=2x-3 | | 4/-6+2=-1 | | 3(x)=2x-3 | | 3(6x-4)-4(x+7)=6x-96+x | | 4(4x+1)=3x-4(6-x)8 | | 2.75(x)=2x-3 | | -7(x-2)=-4 | | 0.86=exp(-6.2831*f) | | 0.86=exp(-2*pi*f) | | (3x-2)2=(2x+3)2 | | 9^4x*27^2-3x=1/9 | | x^5x^7/x^6 | | 5-2q=3Q |

Equations solver categories